MG53 alleviates hypoxia/reoxygenation-induced cardiomyocyte injury by succinylation and ubiquitination modification - Yan Wang; Hongying Zhou; Jin Wu; Shanshan Ye (Clinical and Experimental Hypertension, 2023)
Background Mitsugumin 53 (MG53) is a membrane repair factor that is associated with acute myocardial infarction. This study aimed to investigate the effects of MG53 on cardiomyocyte injury and the posttranslational modification of MG53. Methods Cardiomyocyte injury was evaluated by enzyme-linked immunosorbent assay and flow cytometry. The succinylation and ubiquitination levels of MG53 were examined by immunoprecipitation (IP) and western blot. The relationship between MG53 and KAT3B or SIRT7 was assessed by co-IP and immunofluorescence. Results The results showed that overexpression of MG53 inhibited inflammation response and apoptosis of cardiomyocytes induced by hypoxia/reoxygenation (H/R). Succinylation and protein levels of MG53 were downregulated in H/R-induced cells, which was inhibited by SIRT7 and promoted by KAT3B. SIRT7 aggravated and KAT3B alleviated MG53-mediated cardiomyocyte injury. Moreover, MG53 was succinylated and ubiquitinated at K130. Conclusion SIRT7 inhibited/KAT3B promoted succinylation of MG53 at K130 sites, which suppressed ubiquitination of MG53 and upregulated its protein levels, thereby alleviating H/R-induced cardiomyocyte injury. The findings suggested that MG53 may be a potential therapy for myocardial infarction.